REVIEW ARTICLE : AKTIVITAS FARMAKOLOGI DAN SENYAWA KIMIA PADA TANAMAN KANGKUNG PAGAR (Ipomoea carnea Jacq.) - Aan Setia Asih; Indriyani; Vinkan Kemala Kurnia; Neni Sri Gunarti (Jurnal Buana Farma, 2022)
Ipomoea carnea which is a member of the Convolvulaceae family. Ipomoea carnea is known as a hedge plant and in recent times it is commonly known as a weed. This plant can live in terrestrial areas or near water or puddles. Ipomoea carnea contains chemical compounds, among others, flavonoids, phenols, tannins, saponins, alkaloids, and polyphenols. using a literature review study method that was reviewed based on 25 journals. The results from various studies showed that Ipomoea carnea plant has pharmacological activities such as antioxidant, anti-inflammatory, antidiabetic, anticancer, antifungal, hepatoprotective activity, and immunomodulator.